Exploring Artificial Intelligence and Machine Learning Methods for Facial Detection and Recognition - Arpita Vishwakarma,; Neha Anand,; Dr. Yusuf Perwej,; Neeta Bhusal Sharma, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Facial detection and identification have become essential technologies in computer vision, artificial intelligence, and biometric authentication. These systems detect and authenticate human faces using digital photos or video frames, serving a vital function in security, surveillance, social media, and tailored user experiences. Facial detection involves identifying faces within an image, while facial recognition extends this by correlating identified faces with stored data to verify identification. Facial recognition technology, a significant application within artificial intelligence, has substantial promise for advancement in security surveillance, mobile computing, and other domains. Recent breakthroughs in deep learning, convolutional neural networks (CNNs), and machine learning algorithms have markedly improved the precision and efficiency of these systems. Notwithstanding the advancements, obstacles such as fluctuations in illumination, facial emotions, age, and occlusion continue to impact performance. This study examines the methodology, applications, and limits of face detection and recognition systems, as well as ethical problems and privacy consequences. The growing integration of mobile devices, intelligent surveillance systems, and digital verification platforms is anticipated to influence the future of human-computer interaction. Current research seeks to enhance real-time recognition skills and rectify biases to make these systems more inclusive and dependable. These factors are essential for the responsible development of face recognition technology, assuring ethical practices and protecting privacy.
Keywords: Biometrics; Facial Detection; Facial Recognition; Computer Vision; Biometric Authentication; Machine Learning; Human-Computer Interaction